Preparation, characterization, and water-sorption study of polyvinyl alcohol based hydrogels with grafted hydrophilic and hydrophobic segments - Shukla, S.; Bajpai, A. K.; Kulkarni, R. A. (Journal of Applied Polymer Science, 2005)
The interpenetrating polymer network hydrogels based on poly(vinyl alcohol) were obtained by graft copolymerization of acrylamide and styrene onto polyvinyl alcohol in the presence of N,N'-methylene bisacrylamide as a crosslinking agent. The hydrogels were characterized by optical microscopy, scanning electron microscopy, infrared spectral analysis, differential scanning calorimeter, and thermogravimetric analysis. The hydrogels showed enormous swelling in aqueous medium and displayed swelling characteristics, which were highly dependent on the chemical composition of the hydrogels and pH of the swelling medium. The kinetics of water uptake and the mechanisms of water transport were studied as a function of composition of the hydrogel and pH of the swelling medium. (C) 2005 Wiley Periodicals, Inc.
Keywords: Characterization; equilibrium swelling; grafting; IPN hydrogels; polyvinyl alcohol

Comparing ultraviolet and chemical reduction techniques for enhancing photocatalytic activity of silver oxide/silver deposited nanocrystalline anatase titania - Priya, R.; Baiju, K. V.; Shukla, S.; Biju, S.; Reddy, M. L. P.; Patil, K.; Warrier, K. G. K. (Journal of Physical Chemistry C, 2009)
Silver oxide/silver have been deposited, with varying silver concentration (0.01-10 mol %), on the surface of sol-gel derived nanocrystal line anatase titania using two different techniques, namely the ultraviolet reduction and chemical reduction (using stannous ions). The pure and silver oxide/silver-deposited nanocrystalline anatase titania have been characterized for their morphology, average nanocrystal lite size, specific surface area, phases involved, surface chemistry, band gap, and photoluminescence using various analytical techniques, such as scanning electron microscopy, transmission electron microscopy, Brunauer, Emmett, and Teller surface-area measurement, X-ray diffraction, X-ray photoelectron spectroscopy, ultraviolet-visible spectrophotometry, and spectrofluorometry, respectively. The photocatalytic activity of pure and silver oxide/silver-deposited nanocrystalline anatase titania has been measured by monitoring the degradation of methylene blue dye in an aqueous solution under ultraviolet-radiation exposure. Within the investigated Ag-concentration range, the maximum photocatalytic activity has been observed for 0.1 and 10 mol % Ag for the chemical-reduction (using stannous ions) and ultraviolet-reduction methods with the corresponding apparent first-order reaction-rate constant (k(app)) values of 0.228 and 0.151 min(-1), which are 3.5 and 2.3 times larger than that of pure nanocrystalline anatase fitania (0.065 min(-1)). The chemical-reduction method (using stannous ions), hence, appears to be more effective than the ultraviolet-reduction method for enhancing the photocatalytic activity of nanocrystalline anatase titania. Various factors such as the surface concentration of superoxide ions, oxygen-ion vacancies, and stannous ions as well as the amount of silver oxide/silver and tin oxide are observed to control the surface-adsorption of methylene blue and photoinduced electron/hole lifetime and, hence, variation in the photocatalytic activity as a function of silver concentration.

Enhanced solar-radiation induced photocatalytic activity of surface-modified nanocrystalline anatase-titania - Priya, R.; Baiju, K. V.; Shukla, S.; Biju, S.; Reddy, M. L. P.; Patil, K. R.; Warrier, K. G. K. (Catalysis Letters, 2009)
Sol-gel derived pure nanocrystalline (similar to 20-30 nm) anatase-titania has been surface-modified by depositing silver(I) oxide and silver (predominantly the former) via UV-reduction process. The pure and surface-modified nanocrystalline anatase-titania have been characterized using different analytical techniques for determining the average nanocrystallite size, phase-contents, surface-chemistry, as well as the absorption and photoluminescence characteristics. It is demonstrated that, the latter exhibits an enhanced solar-radiation induced photocatalytic activity as compared to that of the former as a result of the absorption in the visible-region and enhanced photo-induced e(-)/h(+) life-time, both caused by the surface-deposition of silver(I) oxide and silver.
Keywords: Nanocrystalline; Photocatalysis; Silver; sol-gel; titania; UV-reduction

Novel electroless process for copper coating of flyash using titania/ultraviolet-radiation/metal catalyst-system - Shijitha, T.; Baiju, K. V.; Shukla, S.; Patil, K.; Warrier, K. G. K. (Applied Surface Science, 2009)
A novel electroless process has been demonstrated in this investigation to coat the surface of flyash particles with a conducting metal such as copper. The conventional electroless process has been modified for this purpose by replacing the tin-palladium catalyst-system with the titania/ultraviolet-radiation/metal catalyst-system, where the metal is either copper or silver as demonstrated here. The mechanism of copper coating of flyash particles in an electroless bath, using the novel methods of surface-sensitization and surface-activation, has been systematically studied by monitoring changes in the surface-morphology, surface-chemistry, and surface-structure of flyash particles using the scanning electron microscope, energy dispersive analysis of X-rays, X-ray photoelectron spectroscope, and X-ray diffraction. It has been revealed that the novel electroless method involves coating the flyash particles with titania photocatalyst via sol-gel, which acts as a surface-sensitizer under the ultraviolet-radiation exposure for the subsequent surface-activation with the copper- or silver-clusters. The latter in turn acts as surface-catalyst for the subsequent Cu-coating in an electroless bath. The proposed mechanism of surface-sensitization and surface-activation of flyash particles using the novel catalyst-system has been compared with that using the conventional catalyst-system. (C) 2009 Elsevier B. V. All rights reserved.
Keywords: Copper; Electroless; Flyash; Photocatalysis; sol-gel; titania